Cultura, represión y subversión, sentido de los movimientos estudiantiles en México en los años sesentas - Ballesteros Olivares, Hiram (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
When intending this investigation we leave of the possible influence of the thought of the Critical theory and especially of Marcuse in the juvenile revolts of the years 60' of the one XX century in several countries of the world and particularly in Mexico, preceded of student movements in several universities like Puebla, Sinaloa, the Institute Polytechnic National and our University Michoacana in 1963 and 1966, facts that they left in our generations many experiences about the reality of that time, him that it motivated us to meditate on them, not so much in the historical of their story, as much as in the search of their sense. With my tutor we believed convenient to describe the ideas fundamental of the School of Frankfurt and of their members, the intellectual biography of our philosopher and the analysis of two of their fundamental works related with our investigation, in them Marcuse crumbles the industrial contemporary society and us he/she speaks that of the dominance principles and of the liberation possibilities, hence we approach their ideas to know if they influenced in those so important events in that time. A possible dialogue between our author and the writer Revolved José is hardly sketched at the end and he/she transforms into an attractiveness he/she fears for another work.

Al proponernos esta investigación partimos de la posible influencia del pensamiento de la Teoría Crítica y especialmente de Marcuse en las revueltas juveniles de los años 60` del siglo XX en varios países del mundo y particularmente en México, precedidos de movimientos estudiantiles en varias universidades como Puebla, Sinaloa, el Instituto Politécnico Nacional y nuestra Universidad Michoacana en 1963 y 1966, hechos que dejaron en nuestras generaciones muchas experiencias sobre la realidad de ese tiempo, lo que nos motivó para reflexionar sobre ellos, no tanto en lo histórico de su relato, cuanto en la búsqueda de su sentido. Con mi tutor creímos conveniente describir las ideas fundamentales de la Escuela de Frankfurt y de sus integrantes, la biografía intelectual de nuestro filósofo y el análisis de dos de sus obras fundamentales relacionadas con nuestra investigación, en ellas Marcuse desmenuza la sociedad industrial contemporánea y nos habla la de los principios de dominación y de las posibilidades de liberación, por ello abordamos sus ideas para saber si influyeron en esos sucesos tan importantes en esa época. Un posible diálogo entre nuestro autor y el escritor José Revueltas se esboza apenas al final y se convierte en un atractivo tema para otro trabajo.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2007-0010; Herbert Marcuse; Frankfurt; Sociedad; Unidimensional; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/42